Can We Speak of a Regent’s Tradition? A Modest Attempt - Goodliff, Andy (Baptist quarterly, 2025)
This article engages with the writings of three principals of Regent's Park College, once the college had moved to Oxford in 1927: Henry Wheeler Robinson, Barrie White, and Paul Fiddes. It seeks to discern a ‘Regent's tradition’ regarding the purpose of education, namely theological and ministerial. It argues this is best captured an emphasis on the formation of intellect within a broad horizon and the formation of the person within community within a context of Baptist identity.